2022
DOI: 10.1155/2022/6095441
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Value of sTREM-1, PCT, and 1,3-β-D Glucan in Diagnosis of Immune-Associated Pulmonary Interstitial Disease with Fungal Infection

Abstract: Background. Fungal infection in the lungs can cause fungal infectious diseases. This disease develops rapidly and involves a wide range. Pathogenic fungi are also more serious types of pathogenic bacteria. If it invades deep organs and tissues, it will endanger life, so it needs timely diagnosis. Aim. To investigate the diagnostic value of serum soluble myeloid cell triggering receptor-1 (sTREM-1), procalcitonin (PCT), and 1,3-β-D glucan detection in immune related lung disease complicated with fungal infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%